The effectiveness of using webtoon-based comic media on student’s math anxiety - Syofyana, Elza Dewi; Indriani, Hesti; Safitri, Vira; Khairunnisa, Athagian Salma; Husna, Asmaul (CAHAYA PENDIDIKAN, 2025)
The background of this research is based on the high level of students’ anxiety toward mathematics, especially in physiological, cognitive, and behavioral aspects. The ethnomathematics approach is used to connect the concept of sets with local cultural elements through the Makyong dance. This study aims to examine the effectiveness of Webtoon comic learning media based on ethnomathematics and Makyong dance in reducing math anxiety among Hang Nadim Batam vocational school students on the topic of sets, with a sample of 17 students from a population of 66 eleventh-grade students. The research method used is a quasi-experiment with a one-group pretest-posttest design. The research instrument is a math anxiety questionnaire analyzed using the Wilcoxon Signed Rank Test and N-Gain. Based on the Wilcoxon Signed Rank Test results, the Z value = -3.624 with Asymp. Sig. (2-tailed) = 0.000. Since the Asymp. Sig. (2-tailed) < α (0.000 < 0.05), H is rejected and H₁ is accepted. The results show a decrease in students’ math anxiety, with an average pretest score of 41.71 and a posttest score of 74.88. The average N-Gain score of 0.56 indicates a moderate level of effectiveness. Thus, the use of Webtoon comic learning media based on ethnomathematics and Makyong dance is proven to be quite effective in significantly reducing students’ math anxiety.